Comparison of land suitability class for endemic Coffea liberica Pinogu HP. acquired using different methods and recommendations for land management in Pinogu Plateau, Bone Bolango Regency, Indonesia - Nurdin Nurdin; Fauzan Zakaria; Mohammad A Azis; Yunnita Rahim; Rival Rahman; Mahmud Kasim (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
Coffee is a national strategic commodity that contributes to Indonesia’s foreign exchange, but its productivity remains low due to cultivation on low potential land. This study aimed to determine the land suitability of endemic liberica coffee using two different methods and formulate recommendations for land management in Pinogu Plateau. Thirteen land units were surveyed, and soil samples were collected and analyzed in the laboratory to identify the land characteristics. Land suitability classes (LSCs) were compared by limiting factor and parametric methods. Analysis using the limiting factor method showed that the actual LSCs for liberica coffee consisted of moderately suitable (S2) and marginally suitable (S3) classes. Efforts for improvement could increase the potential of LSC to became very suitable (S1) and S2 classes. Meanwhile, the assessment with the parametric method indicated that the LSC consisted of S1, S2, and S3 classes. These results revealed that the parametric method provides more realistic land characteristics than the limiting factor method. Land management II  or the land that had a little limiting factor turned out to be more dominant with the recommendation of adding P and organic fertilizer.